Ocorrência da cesárea segundo os critérios de Robson em coortes em São Luís-MA e Ribeirão Preto-SP - BOTENTUIT, Thais Natalia Araujo (2021)
Introduction: The cesarean section correctly indicated, contributes to the decrease in the rate of maternal and perinatal morbidity and mortality. Although safe, it involves risks such as bleeding, thromboembolic events, infections and chronic pain. The ideal rate of cesarean sections varies between 10% and 15% according to the World Health Organization (WHO), with rates higher than 10% showing no benefit in reducing maternal and neonatal mortality. Therefore, WHO suggested using the Robson classification to improve the standard for assessing and monitoring cesarean rates. This classification, distributes all pregnant women in 10 groups in ascending order of probability of evolution to cesarean section. The groups, divided according to obstetric characteristics such as: parity, previous cesarean section, beginning of labor, gestational age, fetal presentation and number of fetuses, help to optimize cesarean section indications and interpret the profile of deliveries performed in health services . Objective: To analyze cesarean delivery according to Robson's criteria in two birth cohorts in São Luís - MA and Ribeirão Preto-SP. Method: This is a descriptive study based on data from the study “Etiological factors of preterm birth and consequences of perinatal factors on child health: birth cohorts in two Brazilian cities - BRISA”, carried out in the cities of São Luís - MA and Ribeirão Preto- SP. The sample of São Luís was composed by 5166 births and Ribeirão Preto by 7660 births. The analysis of the data collected for the present study will be carried out in the STATA / SE 14.0 program. Descriptive analyzes were performed in the form of absolute and relative frequencies. Results: There were 5166 births in the city of São Luís and 7658 in the city of Ribeirão Preto in the studied period. Of these, 47.52% were cesarean sections in the city of São Luís and 59.82% in Ribeirão Preto. Cesarean rates are higher among women with better socioeconomic conditions, women of white color, aged between 20 and 34 years. When distributing pregnant women into the 10 Robson Classification groups, it is noted that the highest occurrence of births occurred in group 4 and cesarean section in group 4 (multiparous, without previous cesarean section, with single fetus, cephalic, greater or equal at 37 weeks, whose delivery is induced or who undergo a cesarean section before the start of labor) and 5 (all multiparous women with at least one previous cesarean section, with a single fetus, cephalic, greater than or equal to 37 weeks). : Thus, in order to reduce cesarean sections, one must first invest in reducing the prevalence of cesarean sections among women with previous cesarean sections, as it is the most important determinant for the increase in cesarean rates in the world. The implementation of the Robson Classification is the first step towards the critical evaluation of obstetric practice and its results can guide the creation of specific strategies for each group that needs to optimize cesarean rates.